Comparison of GenXpert MTB/RIF Test and Traditional Methods in Pulmonary and Extrapulmonary Specimens for Rapid Diagnosis of Tuberculosis - Gunbey, Fatma; Asci-Toraman, Zuelal (Doc Design Informatics Co Ltd, 2024)
Objective: Tuberculosis (TB) is the leading cause of morbidity and mortality worldwide. Tuberculosis is difficult to control due to the lack of simple, rapid and at the same time accurate diagnostic tests. Molecular diagnostic techniques are of great importance in the new tuberculosis control strategy of the World Health Organization. In this study, the GeneXpert MTB/RIF assay's performance for detecting Mycobacterium tuberculosis (MTB) was compared with conventional methods. Methods: Pulmonary and extrapulmonary specimens sent to laboratory during 2020 were included in the study. A total of 379 specimens were routinely examined for the presence of acid-fast bacilli and then cultured in Lowenstein-Jensen (LJ) and Mycobacterium Growth Indicator Tubes (MGIT) (Becton Dickinson, USA). The prepared samples were analyzed using the GeneXpert MTB/RIF Test (Cepheid, USA). The GenoType Mycobacterium CM test kit (Hain Lifescience, Germany) was used in case of a clinical request for species identification of patient samples with non-tuberculous mycobacteria (NTM) identification. The results were compared to assess the performance of the GeneXpert MTB/RIF test. Results: A total of 1 (0.2%) of 379 pulmonary and extrapulmonary samples had a positive smear result; 21 (5.5%) of 378 samples with negative smear results had growth in culture, and all were confirmed positive by GeneXpert MTB/ RIF test. Of the 22 samples with positive test results, 21 (95.4%) were susceptible to RIF, and 1 (4.6%) was resistant. Using the results of the BD BACTECTM MGITTM 960 (Becton Dickinson, USA) as a reference, statistical analyses were performed with the limited data available and the specificity, sensitivity, positive predictive value and negative predictive value of GeneXpert test were calculated as 98%, 68%, 68% and 98%, respectively. Conclusion: The GeneXpert test showed higher sensitivity than ADB smear microscopy for the detection of MTB in pulmonary and extrapulmonary samples. Early detection facilitates the control of disease transmission and the timely initiation of TB treatment. In this context, the implementation of the GeneXpert test will significantly reduce the number of multidrug-resistant TB cases.
Tüberkülozun Hızlı Tanısı İçin Pulmoner ve Ekstrapulmoner Örneklerde GenXpert MTB/RIF Testi ve Geleneksel Yöntemlerin Karşılaştırılması
Keywords: Mycobacterium tuberculosis; GeneXpert MTB/RIF; Bactec 960TB; rifampicin resistance